2021
DOI: 10.1080/08964289.2021.1946468
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimization and relationships to approach and avoidance coping to health and health behaviors

Abstract: Peer victimization during high school is a common experience associated with engagement in risky health behaviors and elevated depressive symptoms. Mechanisms linking peer victimization to health outcomes remain inadequately understood. in the current study, latent class analysis was used to identify latent subclasses of college students who display similar patterns of responses to frequent peer victimization experiences during high school. We also examined moderating and mediating effects of coping (approach/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…After identifying the clusters, the impact of bullying on adolescent were suicidal behaviour, 12 mental disorder, 13 NSSI, 14 loneliness, 15 psychological distress 16 and ACEs. 17 From overlay visualisation, it was indicated that the newest topics that were widely researched related to the impact of bullying on adolescents were social anxiety, 18 suicidal ideation, 19 depressive symptoms, 20 suicidal thoughts, 21 integrated behaviour change (IBC) 22 and peer victimisation. 23 From density visualisation, it was indicated that topics that were rarely researched related to the topic of the impact of bullying on adolescents were suicide attempts, 24 early victimisation, 25 post-traumatic stress disorder (PTSD) 26 and suicidality.…”
Section: Discussionmentioning
confidence: 99%
“…After identifying the clusters, the impact of bullying on adolescent were suicidal behaviour, 12 mental disorder, 13 NSSI, 14 loneliness, 15 psychological distress 16 and ACEs. 17 From overlay visualisation, it was indicated that the newest topics that were widely researched related to the impact of bullying on adolescents were social anxiety, 18 suicidal ideation, 19 depressive symptoms, 20 suicidal thoughts, 21 integrated behaviour change (IBC) 22 and peer victimisation. 23 From density visualisation, it was indicated that topics that were rarely researched related to the topic of the impact of bullying on adolescents were suicide attempts, 24 early victimisation, 25 post-traumatic stress disorder (PTSD) 26 and suicidality.…”
Section: Discussionmentioning
confidence: 99%